Membangun Kesadaran Lingkungan Melalui Kurikulum Pendidikan Islam Kontribusi terhadap SDGs - Firdaus, Fauzan Akmal (TarbiyahMU, 2024)
Islamic education has the potential to support the achievement of sustainable development goals (SDGs), but challenges in its implementation still hinder its optimal contribution. This research aims to explore how Islamic education values can be integrated with the principles of the SDGs and to identify challenges and opportunities. Using a descriptive qualitative literature study method, this research analyzes articles from reputable journals that discuss the integration of Islamic education in the context of the SDGs. The results show that while there is alignment between Islamic values and the goals of the SDGs, practical implementation is often hampered by limited resources and policy support. The findings enrich understanding of the role of values-based education in sustainable development and offer guidance for educators and policymakers. Implications of this study include the need for more inclusive curriculum development, greater policy support and continued research to address implementation challenges and maximize Islamic education's contribution to the SDGs. Keywords: Islamic Education, Sustainable Development, Environmental Awareness, Curriculum Integration